A New Keynesian Model of the Armenian Economy - Stepanyan, Ara.; Dabla-Norris, Era.; Mkrtchyan, Ashot (Washington, D.C. : International Monetary Fund, 2009)
This paper develops a small open economy dynamic stochastic general equilibrium (DSGE) model of the Armenian economy. The structure of the model is largely motivated by recent developments in DSGE modeling, with key extensions to incorporate specific structural characteristics of the Armenian economy. The resultant model can be used to simulate monetary policy paths and help analyze the robustness of policy conclusions. The paper tests the model's properties on Armenian data, demonstrating that the main stylized features relevant for monetary policy making are well captured by the model.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet